The THE ANALYSIS OF THINKING STYLE AND CONFIDENCE LEVEL IN SOLVING PHYSICS PROBLEMS - Rahayu, Ria; Saminan, Saminan; Mursal, Mursal (Unnes Science Education Journal, 2018)
The ability to solve problems is a vital part to be developed for students in the teaching and learning process. The objective of this research was to identify different stages of ability in solving physics problems regarding thinking styles and confidence level and the correlation between the two variables and the ability to solve physics problems. A quantitative method with the cross-sectional design was used in this research. All of the second-grade students in natural science program of State Senior High School 5 Banda Aceh ware the population members while 30 students ware chosen as the samples by using random sampling technique. A test measuring the ability to solve physics problem and a questionnaire measuring thinking style and confidence level of the students ware used as the research instruments. The data that had been collected ware then analyzed by using one way ANOVA test. The results indicated that there was a significant difference in the ability to solve physics problems regarding thinking style and confidence level of the students. Moreover, it was also found that there was a correlation between the two variables and the ability to solve the physics problem.